SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84118-ms
|View full text |Cite
|
Sign up to set email alerts
|

High Power/High Frequency Acoustic Stimulation – A Novel and Effective Wellbore Stimulation Technology

Abstract: Reduced production is often caused by local impairment of the formation permeability due to the interaction of the reservoir with drilling and completion fluids. The problem may be further compounded by impairment caused by fines migration during production. High frequency sonic and ultrasonic waves have been used in many industrial applications to remove contaminants like dirt, oil, and grease from parts immersed in fluids. An obvious extension of this application is the removal of wellbore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Such well are sure to be benefited form acoustic stimulation method that eliminates the need of aggressive chemicals and difficulties associated with the fluid placement, diversion and penetration into the formation. Tests (1)(2)(3)(4)(5)(6)(7)(8)(9) indicate that potential is greatest in fields with high water-cut and large amounts of immobile oil, making mature domestic reservoirs a prime target Instead of invading near wellbore formation with acids and chemicals, it is now possible, perhaps even desirable to perform stimulation while producing i.e., Underbalance well stimulation. Thus, eliminating issues such as compatibility between injected fluid and in-situ rock/fluid and even surface equipment .In addition, realtime monitoring of productivity is also possible while acoustic stimulation is being carried out.…”
Section: Acoustic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such well are sure to be benefited form acoustic stimulation method that eliminates the need of aggressive chemicals and difficulties associated with the fluid placement, diversion and penetration into the formation. Tests (1)(2)(3)(4)(5)(6)(7)(8)(9) indicate that potential is greatest in fields with high water-cut and large amounts of immobile oil, making mature domestic reservoirs a prime target Instead of invading near wellbore formation with acids and chemicals, it is now possible, perhaps even desirable to perform stimulation while producing i.e., Underbalance well stimulation. Thus, eliminating issues such as compatibility between injected fluid and in-situ rock/fluid and even surface equipment .In addition, realtime monitoring of productivity is also possible while acoustic stimulation is being carried out.…”
Section: Acoustic Stimulationmentioning
confidence: 99%
“…Studies on acoustic cleaning with respect to wellbore stimulation have been presented (1)(2)(3)(4)(5)(6)(7)(8)(9) at various SPE conferences. However, the precise mechanisms responsible for the cleaning action are complex and investigation is still going on.…”
Section: Nearwell Bore Cleaningmentioning
confidence: 99%
“…The predicted drop dimensions matched closely with the experimental observations. Besides its promising role in enhancing phase mobility in porous media, high power ultrasound may also reduce formation damage caused by fines and drilling mud solids, and help mobilize clays in rocks, thus increasing rock permeability and porosity [60][61][62][63][64][65][66][67]. Venkitaraman et al [60] conducted a series of laboratory experiments to investigate the feasibility of using ultrasound to remove formation damage caused by water-based drilling mud and fines.…”
Section: Spe-106521-stu (Student 5)mentioning
confidence: 99%
“…Roberts et al [61] showed that ultrasonic energy can be effectively applied to reduce near-wellbore damage caused by organic deposits and polymers by suspending paraffin deposits and restoring the effective permeability of the rock. Wong et al [67] tested a prototype oval-mode downhole ultrasonic emitter, and determined the required acoustic power to remove fines and particles plugging the near wellbore region. Poesio and Ooms [64] and Poesio et al [65] developed an extensive theoretical model to predict removal of small particles and fines in porous media.…”
Section: Spe-106521-stu (Student 5)mentioning
confidence: 99%
“…It is not always possible to prevent formation damage completely, and well stimulation techniques to remove or mitigate the impact of formation damage have been used in the industry for more than half century (2).…”
Section: Introductionmentioning
confidence: 99%